Surgical resection of intracranial cavernous hemangioma located at uncommon location: Clinical presentation and management - Li, Jiuhong; Zhang, Guisheng; Ma, Qiang; Li, Xiang; He, Jiaojiang (Frontiers in Neurology, 2023)
Background: Intracranial cavernous hemangiomas (CHs) usually originate from cerebral and cerebellar hemispheres, while the clinical features and optimum treatment of CHs originate from atypical locations remain ill-defined. Methods: We conducted a retrospective analysis of CHs originated from sellar, suprasellar or parasellar region, ventricular system, cerebral falx or meninges who underwent surgery from 2009 to 2019 in our department. Results: Fourteen patients of CHs with uncommon locations (UCHs) with pathological confirmation were enrolled in our study and 5 located at sellar, or parasellar region, 3 suprasellar region, 3 ventricular system and 2 cerebral falx and 1 originated from parietal meninges. The most common symptom was headache and dizziness (10/14); none presented with seizure. All UCHs located at ventricular systems and 2 of 3 UCHs located at suprasellar region manifested as hemorrhagic lesion and share similar radiological features compared with axial CHs; other locations of UCHs did not have a “popcorn” appearance on T2-weighted image. Nine patients achieved GTR, 2 achieved STR and 3 achieved PR. Four of five patients underwent adjuvant gamma-knife radiosurgery who received incomplete resection. During average follow-up of 71.1 ± 43.3 months, no patient died, and one patient encountered recurrence and de novo formation of midbrain CH. Most patients had an excellent KPS score of 90-100 (9 of 14) or good KPS score of 80 (1 of 14). Conclusions: We hold that surgery is optimum therapeutic method for UCHs located at ventricular system, dura mater and cerebral falx. Stereotactic radiosurgery plays an important role in the treatment of UCHs located at sellar or parasellar region and remnant UCHs. Favorable outcome and lesion control could be achieved by surgery.